2015
DOI: 10.1007/s11060-015-1930-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary gliosarcomas: clinical, molecular and survival characteristics

Abstract: Gliosarcoma is classified by the World Health Organization as a variant of glioblastoma. These tumors exhibit biphasic histologic and immunophenotypic features, reflecting both glial and mesenchymal differentiation. Gliosarcomas can be further classified into primary (de novo) tumors, and secondary gliosarcomas, which are diagnosed at recurrence after a diagnosis of glioblastoma. Using a retrospective review, patients seen at MD Anderson Cancer Center between 2004 and 2014 with a pathology-confirmed diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
59
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 44 publications
10
59
3
Order By: Relevance
“…Notwithstanding, limited but stepwise discoveries are optimizing treatment protocols, as in the specific example of GS frequently lacking the overexpression of epidermal growth factor receptor (EGFR) seen in IDH-wildtype GB, which challenges the utility of anti-EGFR modalities in GS treatment [19]. Still other studies of the molecular alterations in GS have found a high incidence of TP53 mutations, as well as rare EGFR and IDH mutations [20, 21]. Further study of the molecular mechanisms underlying GS development and spread is required to better understand the natural history and optimal treatment of these lethal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, limited but stepwise discoveries are optimizing treatment protocols, as in the specific example of GS frequently lacking the overexpression of epidermal growth factor receptor (EGFR) seen in IDH-wildtype GB, which challenges the utility of anti-EGFR modalities in GS treatment [19]. Still other studies of the molecular alterations in GS have found a high incidence of TP53 mutations, as well as rare EGFR and IDH mutations [20, 21]. Further study of the molecular mechanisms underlying GS development and spread is required to better understand the natural history and optimal treatment of these lethal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN mutations (15–45%), 4, 9, 10, 11 TP53 mutations (24–73%) 4, 9, 11 and TERT promoter mutations (83%) 10 were common, and IDH1 mutations were rare or absent (0–7%). 10, 11 At the chromosome level, the copy-number alterations (CNAs) that were commonly detected included amplifications of chromosome 7 (75%) and X (20%) as well as deletions of chromosome 10q (88%) and 9p (35%). 4, 10 Amplifications of EGFR and homozygous deletions of CDKN2A were reported in 0–8% 4, 9 and 37–60% 9, 10 of the GS cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular differences of primary IDH-wildtype and IDH-mutant (secondary) GBMs are well summarized in the paper by Cachia et al . [20]. The genetic abnormalities of the IDH-mutant GBMs are similar to grade II/III astrocytomas.…”
mentioning
confidence: 99%